Methadone maintenance treatment and HIV risk-taking behaviour among injecting drug users in Berlin. Issue 5 (October 1996) - Stark, K; Müller, R; Bienzle, U; Guggenmoos-Holzmann, I
Abstract : STUDY OBJECTIVE: To determine whether methadone maintenance treatment (MMT) is effective in reducing the levels of HIV risk-taking behaviour (borrowing and lending of injection equipment, irregular condom use) among injecting drug users (IDUs), and to identify independent predictors of the borrowing of used syringes. DESIGN: Cross sectional study of IDUs in MMT and not in MMT, using standardised interviews for collection of sociodemographic and behavioural data, and laboratory tests for detecting HIV antibodies. SETTING AND PARTICIPANTS: The 612 IDUs were recruited at different services for drug users such as treatment centres, walk in agencies, a hospital, and on the streets. MAIN RESULTS: Of all IDUs, 41% had borrowed and 34% had passed on used injection equipment in the previous six months. In univariate analysis, IDUs receiving MMT had injected less frequently and were significantly less likely to borrow and lend syringes. In logistic regression analysis, MMT was protective against the borrowing of syringes (adjusted odds ratio 0.36, 95% confidence interval 0.2, 0.8), but not against syringe lending nor against sexual risk behaviour (i.e., numbers of sex partners, lack of condom use). Important independent predictors of the borrowing of syringes were injecting drug use in prison, use of sedatives, and sex with another IDU in the previous six months. CONCLUSIONS: MMT may play a significant role in reducing the levels of borrowing of syringes among IDUs. However, additional prevention measures are needed which should specifically address sexual risk behaviour and target subgroups of IDUs with high levels of needle sharing, such as IDUs who have been in prison and and those who are sedative users.